Periglacial preconditioning of debris flows in the Southern Alps, New Zealand - Sattler, Katrin (11698351) (2014)
The lower boundary of alpine permafrost extent is considered to be especially sensitive to climate change. Ice loss within permanently frozen debris and bedrock as a consequence of rising temperature is expected to increase the magnitude and frequency of potentially hazardous mass wasting processes such as debris flows. Previous research in this field has been generally limited by an insufficient understanding of the controls on debris flow formation. A particular area of uncertainty is the role of environmental preconditioning factors in the spatial and temporal distribution of debris flow initiation in high-alpine areas. This thesis aims to contribute by investigating the influence of permafrost and intensive frost weathering on debris flow activity in the New Zealand Southern Alps. By analysing a range of potential factors, this study explores whether debris flow systems subjected to periglacial influence are more active than systems outside of the periglacial domain. A comprehensive debris flow inventory was established for thirteen study areas in the Southern Alps. The inventory comprises 1534 debris flow systems and 404 regolith-supplying contribution areas. Analysis of historical aerial photographs, spanning six decades, identified 240 debris flow events. Frequency ratios and logistic regression models were used to explore the influence of preconditioning factors on the distribution of debris flows as well as their effect on sediment reaccumulation in supply-limited systems. The preconditioning factors considered included slope, aspect, altitude, lithology, Quaternary sediment presence, neo-tectonic uplift rates (as a proxy for bedrock fracturing), permafrost occurrence, and frost-weathering intensity. Topographic and geologic information was available in the form of published datasets or was derived from digital elevation models. The potential extent of contemporary permafrost in the Southern Alps was estimated based on the statistical evaluation of 280 rock glaciers in the Canterbury region. Statistical relationships between permafrost presence, mean annual air temperature, and potential incoming solar radiation were used to calculate the spatially distributed probability of permafrost occurrence. Spatially distributed frost-weathering intensities were estimated by calculating the number of annual freeze-thaw cycles as well as frost-cracking intensities, considering the competing frost-weathering hypotheses of volumetric ice expansion and segregation ice growth. Results suggest that the periglacial influence on debris flow activity is present at high altitudes where intense frost weathering enhances regolith production. Frost-induced debris production appears to be more efficient in sun-avert than sun-facing locations, supporting segregation ice growth as the dominant bedrock-weathering mechanism in alpine environments. No indication was found that permafrost within sediment reservoirs increases slope instability. Similarly, the presence of permanently frozen bedrock within the debris flow contribution areas does not appear to increase regolith production rates and hence debris flow activity. Catchment topography and the availability of unconsolidated Quaternary deposits appeared to be the cardinal non-periglacial controls on debris flow distribution. This thesis contributes towards a better understanding of the controls on debris flow formation by providing empirical evidence in support of the promoting effect of intense frost weathering on debris flow development. It further demonstrates the potential and limitations of debris flow inventories for identifying preconditioning debris flow controls. The informative value of regional-scale datasets was identified as a limitation in this research. Improvement in the spatial parameterisation of potential controls is needed in order to advance understanding of debris flow preconditioning factors.